(untitled) (GESTIÓN Y TENDENCIAS, 2023)
This article analyzes the design of incentive contracts in private companies based on the Principal-Agent model. It explores how moral hazard and information asymmetry affect performance compensation when the agent’s actions and effort levels are unobservable to the owners. Through the use of a simple economic model, the author demonstrates that uncertainty and subjective performance measurement lead to less powerful incentive schemes. It concludes that, given noisy financial variables or the risk of accounting manipulation by the agent, relational contracts with implicit or subjective performance payments prove to be the optimal solution.